2022
DOI: 10.1021/acsami.2c01346
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Oligo-His Peptides to Magnetic γ-Fe2O3@SiO2 Core–Shell Nanoparticles Promotes Their Access to the Cytosol

Abstract: The endosomal entrapment of functional nanoparticles is a severe limitation to their use for biomedical applications. In the case of magnetic nanoparticles (MNPs), this entrapment leads to poor heating efficiency for magnetic hyperthermia and suppresses the possibility to manipulate them in the cytosol. Current strategies to limit their entrapment include functionalization with cell-penetrating peptides to promote translocation directly across the cell membrane or facilitate endosomal escape. However, these st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The confocal images were also used to quantify and compare the Pearson correlation coefficients (PCC), a coefficient with a value between 0 and 1 (where 0 suggests complete endosomal escape and 1 suggests no endosomal escape) (Figure 5c). 34,35 In collectively analyzing these data, endosomal escape differences were generally not observed between the 48h-Hypoxia and 48h-Normoxia groups as evidenced by statistically identical PCC values of ∼0.63 and ∼0.64, respectively. This finding suggests that differences in endosomal escape are unlikely to be the cause of the observed decrease in FLuc expression in hypoxic vs normoxic cells in Figures 2 and 3.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The confocal images were also used to quantify and compare the Pearson correlation coefficients (PCC), a coefficient with a value between 0 and 1 (where 0 suggests complete endosomal escape and 1 suggests no endosomal escape) (Figure 5c). 34,35 In collectively analyzing these data, endosomal escape differences were generally not observed between the 48h-Hypoxia and 48h-Normoxia groups as evidenced by statistically identical PCC values of ∼0.63 and ∼0.64, respectively. This finding suggests that differences in endosomal escape are unlikely to be the cause of the observed decrease in FLuc expression in hypoxic vs normoxic cells in Figures 2 and 3.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Briefly, confocal imaging was performed on U251 cells [whose nuclei were stained with Hoechst 33342 (blue) and whose endosomes were stained with Lysotracker Deep Red (red) that were treated with fluorescently labeled analogs of LNP 1 [ATTO-488 (green)] under the “48-Hour Treatment Protocol” and “72-Hour Treatment Protocol” (Figure a,b)these studies were performed using LNP 1 as a representative study given the generality of the results that we observed for each cell line with LNP 1–4 in the FLuc expression (Figure ) and cellular association and internalization studies (Figure ), respectively. The confocal images were also used to quantify and compare the Pearson correlation coefficients (PCC), a coefficient with a value between 0 and 1 (where 0 suggests complete endosomal escape and 1 suggests no endosomal escape) (Figure c). , In collectively analyzing these data, endosomal escape differences were generally not observed between the 48h-Hypoxia and 48h-Normoxia groups as evidenced by statistically identical PCC values of ∼0.63 and ∼0.64, respectively. This finding suggests that differences in endosomal escape are unlikely to be the cause of the observed decrease in FLuc expression in hypoxic vs normoxic cells in Figures and .…”
Section: Results and Discussionmentioning
confidence: 99%
“…These results suggest that pHis/LNPs are dispersed throughout the cytoplasm owing to preferred endosomal escape, which might result in diffused and strong fluorescence signals. [ 21 ] To demonstrate endosomal escape ability of pHis/LNPs, localization of LNPs and pHis/LNPs was observed after staining cells with Lysotracker, a fluorescent probe of acidic intracellular organelles, e.g., endosomes and lysosomes. [ 32 ] As shown in Figure 5 , yellow dotted signals were observed in cells with LNPs, indicating localization of LNPs in endosomes and lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…[18,19] The pHis is a polypeptide (pK a of histidine: 6.0-6.4) biodegradable by peptidases in the cytoplasm. [20,21] Considering that the endosomal pH is ≈6.0, the pK a value of ionizable lipids seems to be crucial for endosome escape and siRNA encapsulation. Accordingly, we hypothesized that the addition of pHis to siRNA/LNP might improve endoso-mal escape and gene inhibition due to protonation at an acidic pH.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrated that the CA-PCDP@MNP was superparamagnetic and had good magnetic responsiveness. Meanwhile, the saturation magnetization of CA-PCDP@MNPs was 30.17 emu/g, which was lower than that of γ-Fe2O3 MNPs [27,28], illustrating that γ-Fe2O3 MNPs were deposited on a non-magnetic porous polymer. Although there was a decrease in CA-PCDP@MNP saturation magnetization, it still could be quickly separated and recovered via an external magnetic field.…”
Section: Characterizationmentioning
confidence: 85%